The Effect of Discovery Learning Model on Learning Outcomes of Science XI Class Students on Plant Tissue Material - Setiawan, Bayu; Widyastuti , Tia Sandy Widyastuti; Widyaningrum , Trianik Widyaningrum (JURNAL BIOEDUKATIKA, 2023)
The purpose of learning is certainly in the form of good learning outcomes, and its implementation is usually influenced by several major factors from the teacher when choosing a learning strategy or model. So that research was conducted related to the effect of the discovery learning model on the learning outcomes of students in class XI IPA on plant tissue material. This research is a type of quasi-experimental research, and this research was conducted to see whether or not there is an effect of the application of the discovery learning model on the learning outcomes of students in class XI IPA on plant tissue material. The population used in this study was all students of class XI IPA 1, 4, 5, and 6, totaling 117 students. The data sampling technique at the time of the research was purposive sampling. There are two data collection techniques used in this study, namely: (1) written tests, namely by giving a pretest before learning and a posttest after learning, (2) the non-test technique is observation. Based on the results of the normality and homogeneity tests, the results showed that the data were not normally distributed because the Sig value on Kolmogorov-Smirnov was 0.00 < 0.05 and not homogeneous. After all, the homogeneity test results showed the result of 0.00, which was < 0.05. Because the data obtained were not normally distributed and not homogeneous, it was continued with the nonparametric test, namely the Wilcoxon test. Based on the results of the Wilcoxon test, the Asymp. Sig. (2-tailed) is 0.000. Because 0.000 is smaller than 0.05, it can be concluded that the hypothesis is accepted. This means that there is an effect of the discovery learning model on the learning outcomes of class XI students in studying plant tissue material.